Comparison of cortisol, depression and stress hormone levels in primary dysmenorhore adolescents with the application of a combination of facial acupressure with classic music therapy - Anggraini, Fitrya Ayu (Alma Ata University Press, 2024)
Background : Constant chronic dysmenorrhea pain, should be screened with a single morning serum cortisol concentration. Uncontrolled pain (acute and chronic) initially indicates high serum cortisol concentrations. Then, one of the factors that can influence pain during menstruation is stress. Objectives : This study aims to assess non-pharmacological interventions for facial acupressure (BL-2, Yin Tang, GV 23, GB 15, Tai Yang, GB 14, Ex Hn4, TE 23, Sang Ming , LI-20, Ex Hn 8, ST-3, Si 18, Du 26, REN 24, JiaCenjiang, SJ21, SJ17, GB-2) combined with Mozart classical music in reducing cortisol levels, depression and stress in dysmenorrhea primary. Methods: This is quantitative research with a quasi-experimental design. The research approach used is pre-post test design. In November 2021-January 2022 at Megarezky University Makassar. There were 42 Adolescents with Primary Dysmenorrhea for respondents to this research. The sample in this study was divided into three groups, namely an intervention group (combination of facial acupressure with classical music) and 2 control groups which were only given classical music and facial acupressure treatment. Data collected included depression and stress. In addition, cortisol levels were checked using an ELISA Kit. Then the data was analyzed using the Paired T-test, while to see the differences if it was normally distributed using the One Way Anova test and if it was not normally distributed using Kruskal-Wallis. Results: The results of the study found that there was a decrease in cortisol levels, depression and stress when given facial acupressure and classical music, but the reduction was more effective if a combination of facial acupressure and classical music.Conclusions: Among the variables of cortisol levels, depression and stress, the combination of facial acupressure and classical music was significantly more effective in improving stress than just giving facial acupressure and classical music.